Industrial Growth and Socio-Economic Impact: An Analysis of Armi's Manufacturing History in the Mongiana Industrial Village of Serre Calabria - Elia Fiorenza (European Scientific Journal, ESJ, 2024)
The Mongiana Arms Factory in Calabria (Italy), built in 1852, constitutes a significant example of 19th century armoury. Designed by Domenico Fortunato Savino, active from 1852 to the mid-1860s, the factory produced 2000-3000 weapons annually for the bourbon army, with a peak of 7000-8000 in periods of maximum production. He introduced the «Mongiana» spring-loaded rifle, replacing the French model of 1842. After the unification of Italy, it lost relevance, being downgraded to a transformation workshop, and later closed. Today, part of the Ecomuseum of the Ironworks and Foundries of Calabria, the building has been under restoration since 2013. The Museum of the Royal Bourbon Ironworks, the result of a careful recovery process, allows for an in-depth exploration of the historical, economic, and technological role of the factory in the panorama of the steel industry of the time.